The Effects of Restating Financial Statements For Price-Level Changes: A Reply. - McIntyre, Edward V. (The Accounting Review, 1975)
In this article, the author presents a reply to the criticism of his study by researcher Thomas R. Dyckman, which discussed effects of restating financial statements for price-level changes. Dyckman has asserted that the null hypotheses tested in the author's study were false by definition, and therefore the tests performed were trivial. The author argues that this simply is not true. The null hypotheses tested were simulated investment decisions made in a given contest are the same whether based on historical-cost financial statements, current-value financial statements, or a combination of both types of statements; and these decisions, if different, are no "better" when based on any one of the information sets than when based on the other information sets. A considerable portion of Dyckman's comments concern the problems arising from the use of students in a laboratory situation. The limitations arising from these conditions are well known and are adequately acknowledged in the author's study.